The Relationship between Primary Tooth Caries and Stunting in Toddlers - S, Eti Wiyanti; Endarti, Ajeng Tias; Indriyati, Titi (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Stunting is a condition where a child's growth and development are disrupted due to chronic malnutrition. Stunting is a failure of ideal growth caused by a lack of nutrition that lasts for a long time. One of the factors that influences the incidence of stunting is the status of dental caries. Many efforts have been made to prevent stunting, one of which is preventing dental caries. This requires research on the relationship between primary dental caries and the incidence of stunting in toddlers. This study used a sampling method with a random sampling technique and involved 53 respondents. The instrument used was the def-t index to measure dental caries and stunting status based on the TB/U z-score. Statistical analysis was carried out using the chi square test to assess the relationship between dental caries and the incidence of stunting. The results of the study showed that the incidence of very short stunting was less in children with high dental caries, namely 20.8% compared to those with moderate dental caries, namely 55.2%. This means that the incidence of stunting in the very short category has a lower risk in toddlers with high dental caries compared to the moderate category. This study emphasizes the importance of the role of parents in increasing knowledge related to children's health and nutritional status. In addition, parental education and utilization of health service access are important aspects that need to be considered. Health centers, health workers, and the Health Office play an important role in encouraging efforts to control stunting in toddlers.